Composição química e digestibilidade do farelo de arroz vermelho na ração de frangos de corte - Nunes, Vitor Augusto Lopes (Universidade Federal Rural do Semi-Árido, 2019)
The use of alternative poultry feed reduces production costs and enables the utilization of cereal grain processing byproducts, so they should be evaluated and known for composition and digestibility. Rice bran is a byproduct that can be used as an energy source for chickens, but, except for reports and regional experiences, very little has been reported in the literature on the use of red rice bran grown in the western potiguar for poultry. Red rice bran has similarities to white rice bran, for example, relative interference in the availability of minerals such as phosphorus, iron and zinc because of the undesirable chelating action of phytate, in addition to the gelling action of soluble fibrous polysaccharides that may limit digestibility of phytate. other nutrients, but despite this, there are good indications in the utilization of metabolizable energy due to starch and triglyceride contents. The objective of this study was to evaluate the physicochemical composition through laboratory analysis and the digestibility of red rice bran according to the level of inclusion in chicken feed.
Monografia
Keywords: Gallus gallus domesticus; Oryza sativa L.; Nutrição; Nutrition.; CIENCIAS AGRARIAS::ZOOTECNIA